Tingkat Komitmen Kerja Pegawai dalam Pelaksanakan Tugasnya - Syahril Syahril; Sulastri Sulastri (Universitas Negeri Malang, 2023)
Abstract: This research was conducted to determine the level of work commitment of employees in carrying out their duties. This research is descriptive research. The population is 108 employees at the Padang City Education Office. The size of the sample is 67 people taken by using proportional random sampling technique. Data was collected using a questionnaire formulated in the form of a Likert scale, the data was processed with averages and percentages. The results showed that the work commitment of the Padang City Education Office employees was in the moderate category with a percentage of 74.71%. Details of employee work commitment based on indicators, are: 1) responsibility in the sufficient category (79.07%), 2) loyalty in the sufficient category (69.33%), 3) involvement (participation in activities) in the sufficient category (67.87%), 4) the awareness to work is in the sufficient category (78.00%) too, and 5) the feeling of identification is in the sufficient category (79.27%).Keywords: Work Commitment, Implementation of Tasks Abstrak: Penelitian ini dilakukan untuk mengetahui tingkat komitmen kerja pegawai dalam melaksanakan tugasnya. Penelitian ini merupakan penelitian deskriptif. Populasinya adalah 108 pegawai pada Dinas Pendidikan Kota Padang. Besar sampel adalah 67 orang yang diambil dengan menggunakan teknik proportional random sampling. Pengumpulan data menggunakan kuesioner yang dirumuskan dalam bentuk skala likert, data diolah dengan rata-rata dan persentase. Hasil penelitian menunjukkan bahwa komitmen kerja pegawai Dinas Pendidikan Kota Padang berada pada kategori sedang dengan persentase 74,71%. Rincian komitmen kerja pegawai berdasarkan indikator, yaitu: 1) tanggung jawab dalam kategori cukup (79,07%), 2) loyalitas dalam kategori cukup (69,33%), 3) keterlibatan (partisipasi dalam kegiatan) dalam kategori cukup (67,87% ), 4) kesadaran untuk bekerja berada pada kategori cukup (78,00%) juga, dan 5) perasaan identifikasi berada pada kategori cukup (79,27%).Kata kunci: Komitmen Kerja, Pelaksanaan Tugas